APPLICATION OF MODERN INFORMATION TECHNOLOGIES AND METHODS IN TEACHING DRAWING TO SCHOOL STUDENTS - Qobiljonova Jasmina Jasur qizi (Scientific Trends, 2024)
This article discusses the methodology of teaching drawing to schoolchildren and the organization of classes depending on the age and psychology of children of this age, interest, existing knowledge and skills and abilities. Also, the issues of organizing classes using modern information technologies and interactive methods in teaching subjects will be discussed.
Keywords: Drawing, method, teaching, system, demand, image, graphic work, information, efficiency, interactive, tool.